Implication of multiplicity of assignments on women's health (Research, Society and Development, 2021)
Every day, women have expanded their achievements, however, in addition to the possibility of insertion in the labor market and in studies, they took with them several other attributions, such as domestic responsibilities and the act of taking care of children and family, which constitutes a great challenge. Aware of this reality, it is necessary to better understand the conditions of life and health of women, in its integral aspect. In this context, the objective of this study is to understand the effects of the multiplicity of attributions for women's health. It is an exploratory study, with a qualitative approach, anchored in the theoretical-methodological framework of dialectics. Semi-structured questionnaire and interviews were carried out with 17 women aged between 20 and 59 years, who had multiple roles. The data were analyzed by content, in Bardin's perspective. The empirical data revealed that the attributions that most influence the health of women were those that involve the relationship with the house and household chores, with the children and family, and with work. Flexibility and self-care are a challenge for the preservation of well-being and quality of life and maintenance of physical, social and mental balance.